Clinical Practice Guidelines of Mongolian Medicine in Rehabilitation for Cerebral Infarction - Working Group of Clinical Practice Guidelines of Mongolian Medicine in Rehabilitation for Cerebral Infarction; Tuya WULAN; Hao XIN; Rongrong WEN; Qi'e AO; Yongjian ZHAO; Bingbing ZHANG; Jing BAI; Mei FENG; Miaomiao LIU; Liqing SUN; Gula A (康复学报)
Cerebral infarction is a common cerebrovascular disease, which belongs to the category of"Sa disease"in Mongolian medicine. The Mongolian medicine has a special conception for cerebral infarction, its rehabilitation treatment methods are also special and effective. The guideline takes the"three modulation theory"and"brain-white pulse theory"of Mongolian medicine as the guiding ideology, and formulates the standard based on the definition of cerebral infarction, diagnostic points, disease types, syndrome characteristics, syndrome differentiation and treatment, external treatment, rehabilitation training, diet and daily care, etc. The cerebral infarction is divided into five types in Mongolian medicine, such as Heyi, Xila, Badagan, Qisu and Xieriwusu type, and analyzes its pathogenesis, treatment, internal treatment and external treatment in detail. The treatment for cerebral infarction emphasizes that the treatment based on syndrome differentiation, mainly taking Mongolian medicine and combining internal and external treatment. The standardizations have established for the external treatment of Mongolian medicine(acupuncture, bloodletting, cupping therapy, cupping bloodletting, etc.), and as well as the explanation on the methods of early rehabilitation training for cerebral infarction, the principles of rehabilitation training for hemiplegia(good position training, supine up training, seat balance training, knee standing training, kneeling training, form sitting up to standing training, standing balance training, walking training), and the diet and daily care in acute stage and recovery stage. The guidelines are suitable for guiding Mongolian medical professionals to carry out the technical operations of rehabili-tation treatment in a standardized manner. And it is also suitable for standardization work in medical treatment, teaching, scientific research, the relative industry, and international exchanges of Mongolian medicine, which helps to optimize Mongolian medicine-related diagnosis and treatment techniques and enhance the service capabilities of Mongolian medical rehabilitation, with a good clinical applicability, safety and effectiveness.